INNOVANIVE TECHNOLOGIES AS IMPROVING FACTOR OF EDUCATIONAL ACTIVITIES - Urazov, Abduxoliq; Taylanov, Nizom (Физико-технологического образование, 2022)
In this paper we discuss the problem of innovative technologies in educational activity in learning process. We have extensive experience in the use of innovative technologies that increase the educational and creative of students and ensure the effectiveness of the educational process